Exploration and Practice of “Internet + Maker Education” University Innovative Entrepreneurship Education Model From the Perspective of Positive Psychology - Sun, Xiaomeng (Frontiers in Psychology, 2020)
This thesis aims to analyze the importance of psychological quality in the entrepreneurial education for undergraduates in the case of positive psychology, to explore an educational model that combines the Internet information technology with maker education, and to culture the innovative entrepreneurial capabilities of undergraduates. First, the theories of positive psychology were reviewed worldwide, and the current cultivation of entrepreneurial psychological quality for undergraduates was summarized. Second, undergraduates were taken as the survey objects. The questionnaires were distributed both online and offline to investigate the innovative entrepreneurship education (the IE education) in three different universities in Zhejiang Province, China. The current development of IE education in universities was summarized. Finally, according to the current educational status in universities, combining the Internet and maker education, the implementation strategies suitable for IE education in universities was proposed. According to the results of questionnaire survey, the proportion of college students who chose entrepreneurship was 6.1%. The innovation and entrepreneurship of contemporary college students was not optimistic, which was mainly related to the lack of systematic planning and teachers in China's current innovation and entrepreneurship education. Through the integration of internet information technology and maker education, this study constructed a more systematic implementation scheme of innovation and entrepreneurship education in colleges and universities. It could meet the needs of students of different majors and grades. Meanwhile, teachers should give full play to the students' subjective initiative and emphasize the student-centered learning style, thereby promoting the cultivation of students' innovative thinking. The IE education model of “Internet + Maker Education” in colleges can reform traditional college teaching methods, promote the cultivation of entrepreneurship, innovative thinking and creative abilities, and the model can be used as a new idea and method for the development of IE education in universities.